The relationship between NEO personality factors and Hoge's Intrinsic Religious Motivation - Beshai, James A. (Journal of beliefs and values, 2016)
Personality traits have shown variable relationships to measures of religious motivation. For example, Costa and McCrae (1985) and McCrae and Costa (1999) suggested that individuals who are high in agreeableness and conscientious gravitate toward religion once they "meet" with religion as a cultural identity Openness to experience involves varied expressions including sensitivity to aesthetics, and egalitarian values (e.g. McCrae and Costa 1996). As such, it has been shown to be negatively correlated with measures of religious fundamentalism, and positively correlated with intrinsic religious motivation. However, other reviews have found only small correlations between personality and religious motivation. Our study was designed to test the relationships among the Big 5 personality factors with Hoge's Intrinsic Religious Motivation in an undergraduate sample. Results showed that only openness to experience and intrinsic religious motivation were significantly correlated, providing further support for the idea that religious motivation and personality factors may require further research elaboration.